Cholinergic excitation from the pedunculopontine tegmental nucleus to the dentate nucleus in the rat. (11th March 2016) - Vitale, F.; Mattei, C.; Capozzo, A.; Pietrantoni, I.; Mazzone, P.; Scarnati, E.
Highlights: Stimulation of the pedunculopontine tegmental nucleus excited cerebellar nuclei. The excitation was mediated by neuronal cell bodies in the stimulated site. Iontophoretic application of acetylcholine antagonists blocked the evoked response. These data may help to explain deep-brain stimulation effects in motor disorders. Abstract: In spite of the existence of pedunculopontine tegmental nucleus (PPTg) projections to cerebellar nuclei, their nature and functional role is unknown. These fibers may play a crucial role in postural control and may be involved in the beneficial effects induced by deep-brain stimulation (DBS) of brainstem structures in motor disorders. We investigated the effects of PPTg microstimulation on single-unit activity of dentate, fastigial and interpositus nuclei. The effects of PPTg stimulation were also studied in rats whose PPTg neurons were destroyed by ibotenic acid and subsequently subjected to iontophoretically applied cholinergic antagonists . The main response recorded in cerebellar nuclei was a short-latency (1.5–2 ms) and brief (13–15 ms) orthodromic activation. The dentate nucleus was the most responsive to PPTg stimulation. The destruction of PPTg cells reduced the occurrence of PPTg-evoked activation of dentate neurons, suggesting that the effect was due to stimulation of cell bodies and not due to fibers passing through or close to the PPTg. Application of cholinergic antagonists reduced or eliminated the PPTg-evoked response recorded in the dentate nucleus. The results show that excitation is exerted by the PPTg on the cerebellar nuclei, in particular on the dentate nucleus. Taken together with the reduction of nicotinamide adenine dinucleotide phosphate-diaphorase-positive neurons in lesioned animals, the iontophoretic experiments suggest that the activation of dentate neurons is due to cholinergic fibers. These data help to explain the effects of DBS of the PPTg on axial motor disabilities in neurodegenerative disorders.